OP0058 Low-dose radiation therapy as treatment for hand and knee osteoarthritis: two double-blinded rct's. (12th June 2018) - Minten, M.; Mahler, E.; Leseman-Hoogenboom, M.; Boks, S.; Kloppenburg, M.; Leer, J.W.; Poortmans, P.; van den Hoogen, F.; den Broeder, A.; van den Ende, C.
Abstract : Background: Synovial inflammation plays an important role in osteoarthritis (OA) pathophysiology. In some countries, low-dose radiation therapy (LD-RT) is widely used as treatment for OA, while relatively unknown in others. Studies in vitro and in OA animal models have shown anti-inflammatory effects of LD-RT. However, systematic literature review has shown that high-level evidence for beneficial effects in clinical practice is lacking. Objectives: To assess the effect of LD-RT on clinical outcomes and inflammation in patients with hand or knee OA, using two parallel prospective RCTs. Methods: Patients with hand OA (n=56) or knee OA (n=55) according to ACR-criteria, with a pain score ≥5/10, not responding to analgesics and exercise therapy were included. They were randomly allocated 1:1 to the LD-RT (6 × 1 Gy LD-RT in two weeks) or sham (6 × 0 Gy in two weeks) intervention, stratified for pain score (<8 vs≥8). The primary outcome was the number responders according to the OMERACT-OARSI responder criteria, 3 months post-intervention. Secondary outcomes were inflammatory aspects assessed by ultrasound (US; both knee and hand) and MRI (knee only). In hand OA, joints were scored semi-quantitatively (0–3) for US effusion, synovial thickening and power Doppler signal. In knee OA, we assessed the mean US effusion and synovial thickness (mm) at three locations, and the summed MRI effusion/synovitis (semi-quantitatively; 0–3) from four locations. Logistic and linear regression analyses were used to assess differences in dichotomous and continues outcomes, respectively. Analyses were adjusted for pain stratum. Results: Baseline characteristics are shown in table 1. The proportion of responders over time is shown in figure 1. After 3 months, in hand OA, there were 8 (29%) responders in the LD-RT group and 10 (36%) in the sham group (OR 0.69; 95% CI: 0.22 to 2.17). In knee OA, there were 12 (44%) responders in the LD-RT group and 12 (43%) in the sham group (OR 1.09; 95% CI: 0.37 to 3.19). In both hand and knee OA, no significant changes in clinical outcomes and inflammatory aspects were observed in both groups. Conclusions: We were unable to demonstrate a beneficial effect of LD-RT on pain and functioning, nor on inflammatory processes, in patients with hand or knee OA. In light of absence of other high-level evidence, we advise against the use LD-RT as treatment for hand and knee OA. Dutch Trial Register: NTR4574 Disclosure of Interest: None declared